Advertisement calls of 18 anuran species in the megadiverse Atlantic Forest in southeastern Brazil: review and update - Manzano, Maria Carolina Rodella; Takeno, Michele Fernandes; Sawaya, Ricardo J. (Zootaxa, 2022)
Advertisement calls constitute the main acoustic signals emitted by frogs during reproductive seasons and are considered species-specific. Currently, many studies explore the advertisement calls in this group, including descriptions, taxonomy status, influence of social and ecological aspects, character displacement and plasticity. Although some patterns are detected in several anuran species, the possible intra and interpopulation variation is not well established for the group. Furthermore, new approaches have been proposed to standardize studies in the area and contribute to the description and interpretation of anuran calls, highlighting the urgency of a literature review. We aimed to review and update the advertisement calls of 18 anurans species from the megadiverse Atlantic Forest of Southeastern Brazil. We analyzed 1612 advertisement calls from 175 males of 18 anuran species recorded in ten communities between September 2018 and March 2019. We reviewed the information available in 23 scientific papers and describe each advertisement call based on recent papers. Our results include the definition of sound type for all species recorded, providing temporal and spectral parameters for each species along different localities, including intra and interpopulation variations. We provide new information on the frequency range (minimum and maximum frequencies) for eight species. A new description of the advertisement and territorial call of Boana bandeirantes is also provided based on our fieldwork observations. We emphasize that many species present interpopulation variance throughout their distribution in the megadiverse Atlantic Forest. We hope this information will contribute to future research on amphibian anuran bioacoustics and natural history.